PEMBELAJARAN DARING MASA DARURAT COVID-19 PADA MAHASISWA PENDIDIKAN MATEMATIKA - Arbain Arbain; Farman Farman (HISTOGRAM: Jurnal Pendidikan Matematika, 2020)
This research is using descriptive qualitative methods through an online survey. The study was conducted to find an overview of the application of online learning in the Mathematics Education Study Program of the Universitas Sembilanbelas November Kolaka during the Covid-19 emergency. Data collected through questionnaires in the form of Google Forms and interviews by telephone. Data analysis was performed using the Miles & Huberman interactive technique. The results showed that online learning received positive and negative responses from students. Positive responses were obtained from some aspects including the availability of supporting devices, delivery of material, interaction, ease of lecture, time management, class organizing, activeness, independence, and support. Aspects that received negative responses from respondents were assignments, job descriptions and workloads, mastery of the subject materials, internet connection, internet costs, and distraction.